1984
DOI: 10.3109/03008208409013684
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Types I and III Collagen and Fibronectin in the Healing Equine Tendon

Abstract: During tissue response to injury the glycoproteins fibronectin and Type III collagen are synthesized in increased amounts. We have studied the distribution of these molecules in the healing tendon at various times after injury by comparison with that of the major constituent of normal tendon, Type I collagen. Immunofluorescent localization demonstrated the presence of fibronectin throughout the tendon within one week after injury. Staining was found in the matrix, both around capillaries and around fibroblast-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(99 citation statements)
references
References 24 publications
9
89
0
1
Order By: Relevance
“…while a striking increase in the expression of type I procollagen gene was shown both at 7 and at 14 days. Type 111 collagen was reported to be predominantly produced in the earliest phase of wound healing or tendon healing compared with type I collagen [3,8,18]. Our results were consistent with theirs in that gene expression of type 111 procollagen reached a maximum earlier than that of type I.…”
Section: Discussionsupporting
confidence: 91%
“…while a striking increase in the expression of type I procollagen gene was shown both at 7 and at 14 days. Type 111 collagen was reported to be predominantly produced in the earliest phase of wound healing or tendon healing compared with type I collagen [3,8,18]. Our results were consistent with theirs in that gene expression of type 111 procollagen reached a maximum earlier than that of type I.…”
Section: Discussionsupporting
confidence: 91%
“…The tendons in group B appeared macroscopically normal but had a significant increase in fibroiiectin content compared with group A, but not compared with the controls, which may be due to the low number of controls. In this study, as well as in other studies [1, 3,6,16], fibronectin was also shown to be present in normal endotenon. Before fibronectin possibly could serve as a marker for early tendon damage further investigations are necessary.…”
Section: B Tillcinder Rt Ul I Journui Of' Orthilpuedic Rrsrurch 19 supporting
confidence: 67%
“…20,22,25,[41][42][43][44][45] The use of this technique to create a suitable model for the study of naturally occurring tendinitis has been supported by the evaluation of gross and histopathological changes, clinical signs, and ultrasonographic findings following the induction of injury. 44,[46][47][48] In addition, our laboratory has successfully investigated the effects of recombinant IGF-I on equine tendon healing using this collagenase induced model of tendinitis. 20 The histologic, biochemical, and mechanical characteristics of the injured tendons in this study are consistent with those described in previous reports using the collagenase induced model.…”
Section: Discussionmentioning
confidence: 99%